Local similarity solutions of mixed convection stagnation point flow in nanofluid over a vertical stretching or shrinking surface / Noor Adila Othman - Othman, Noor Adila (2018)
The problem of mixed convection boundary-layer flow near a stagnation-point on a perme able and an impermeable stretching or shrinking vertical surfaces immersed in a nanofluid with constant wall temperature and convective boundary condition have been discussed throughout the research. The nanofluid Buongiorno model is employed with an approach of the local similarity solution where the combination of those elements have not been considered before. First, the governing nonlinear equations partial differential equations are reduced to the boundary-layer equations using the boundary-layer and Boussinesq ap proximations. Then, the boundary-layer equations are transformed into a set of ordinary differential equations using the local similarity transformation. Eventually, the ordinary differential equations being solved numerically using a shooting method with the help of Maple 17 software. The effects of the mixed convection parameter A, suction or injection parameter S, stretching or shrinking parameter e, convective heat transfer parameter 7, thermophoresis parameter Nt, Brownian motion parameter Nb, buoyancy-ratio parameter Nr and Lewis number parameter Le on the skin friction coefficient, heat and mass trans fer rate at the surface as well as the velocity, temperature and concentration profiles are analyzed and discussed in details. It is observed that these parameters are significantly af fected and influenced the skin friction coefficient, heat and mass transfer rate at the surface. The results indicate that dual solution exist in a case of the shrinking surface for certain range of the parameters. The results also showed that suctions tends to increase the skin friction coefficient and heat transfer rate at the surface, while injections acts in the opposite manner for both stretching and shrinking surfaces. In contrast, the mass transfer rate at the surface decreases with an increase in suction effect on both stretching or shrinking surface, while injection increases it. In addition, increasing the values of convective heat transfer parameter tends to increase the skin friction coefficient and heat transfer rate at the surface while decrease the mass transfer rate at the surface.